Detrimental Impact of Microbiota-Accessible Carbohydrate-Deprived Diet on Gut and Immune Homeostasis: An Overview - Daïen, Claire Immediato; Pinget, Gabriela Veronica; Tan, Jian Kai; Macia, Laurence (Frontiers in Immunology, 2017)
Dietary fibers are non-digestible polysaccharides functionally known as microbiota-accessible carbohydrates (MACs), only present in insufficient amounts in the Western diet. MACs are a main source of energy for gut bacteria and thus, the abundance and variety of MACs can modulate gut microbial composition and function. This, in turn, impacts host immunity and health. In preclinical studies, the disruption of gut homeostasis and a diet deprived in MACs, aggravate the development of inflammatory diseases such as allergies, infections, and autoimmune diseases. The present review provides an overview of the impact of low MACs diet on gut homeostasis, more precisely on gut microbiota, gut epithelium and immune cells.